Lanthanum Affects Bell Pepper Seedling Quality Depending on the Genotype and Time of Exposure by Differentially Modifying Plant Height, Stem Diameter and Concentrations of Chlorophylls, Sugars, Amino Acids, and Proteins - García-Jiménez, Atonaltzin; Gómez-Merino, Fernando C.; Tejeda-Sartorius, Olga; Trejo-Téllez, Libia I. (Frontiers in Plant Science, 2017)
Lanthanum (La) is considered a beneficial element, capable of inducing hormesis. Hormesis is a dose-response relationship phenomenon characterized by low-dose stimulation and high-dose inhibition. Herein we tested the effect of 0 and 10 μM La on growth and biomolecule concentrations of seedlings of four sweet bell pepper (Capsicum annuum L.) varieties, namely Sven, Sympathy, Yolo Wonder, and Zidenka. Seedling evaluations were performed 15 and 30 days after treatment applications (dat) under hydroponic greenhouse conditions. Seedling height was significantly increased by La, growing 20% taller in Yolo Wonder plants, in comparison to the control. Similarly, La significantly enhanced shoot diameter, with increases of 9 and 9.8% in measurements performed 15 and 30 dat, respectively, as compared to the control. Likewise, La-treated seedlings had a higher number of flower buds than the control. An increase in the number of leaves because of La application was observed in Yolo Wonder seedlings, both 15 and 30 dat, while leaf area was augmented in this variety only 30 dat. Nevertheless, La did not affect dry biomass accumulation. La effects on biomolecule concentration were differential over time. In all varieties, La stimulated the biosynthesis of chlorophyll a, b and total 15 dat, though 30 dat only the varieties Sympathy and Yolo Wonder showed enhanced concentrations of these molecules because of La. Total soluble sugars increased in La-treated seedlings 30 dat. Interestingly, while most varieties exposed to La showed a reduction in amino acid concentration 15 dat, the opposite trend was observed 30 dat. Importantly, in all varieties evaluated, La stimulated soluble protein concentration 30 dat. It is important to note that while chlorophyll concentrations increased in all varieties exposed to La, both 15 and 30 dat, those of soluble sugars and proteins consistently increased only 30 dat, but not 15 dat. Our results confirm that La may improve seedling quality by enhancing some growth parameters and biomolecule concentrations, depending on the genotype, and time of exposure.